Perancangan Aplikasi Document Management System Berbasis Web Universitas Nasional dengan Metode Waterfall - Cut Dinda Rizki Amirillah; Septi Andriyana; Benrahman Benrahman (Universitas Indraprasta PGRI Jakarta, 2020)
One of the most important assets in supporting every work program implemented at the National University community is document management. In the current process, the organization will certainly produce data or documents that are not small with a variety of criteria. The number of physical documents stored in a place sometimes takes a long time to find and borrow the documents needed. The Document Management System (DMS) application is one of the problem solvers that is reliable enough to solve various problems regarding document archiving. In making a website-based DMS application using the Hypertext Preprocessor (PHP) programming language, with the Laravel and Postgres framewok as a database for storing data and using the Waterfall method. The application of DMS which is supported by a website-based application makes the application accessible wherever and whenever, documents are stored centrally, and easily access data between fields